Potencialni učinki kanabinoidov - Štrukelj, Borut (Farmacevtski vestnik, 2016)
Cannabis extracts with high content of cannabinoids have been used for centuries in traditional and official medicine and pharmacy. They were withdrawn from the pharmacopoeia at the beginning of the Second World War and reintroduced in terms of industrial registered medicine in the year 2010 with the indication of spasticity reduction for patients with multiple sclerosis. On-going research studies are in progress in order to confirm the high pharmacological potential of the standardized mixture of natural cannabinoids that can be used for the treatment of pain, multiple sclerosis, epilepsy, stroke, kahexia and anorexia. Even more, some sporadic cases in reduction of solid tumours were observed, however, more clinical studies have to be performed in order to clinically confirm these observations.
Keywords: distonija; Epilepsija; fibromialgija; kaheksija; kanabinoidi; multipla skleroza; therapy; zdravljenje